Systematic psychosocial screening in a paediatric cardiology clinic: clinical utility of the Pediatric Symptom Checklist 17. (1st October 2015) - Struemph, Kari L.; Barhight, Lydia R.; Thacker, Deepika; Sood, Erica
Abstract: Objective: To examine the clinical utility of the Pediatric Symptom Checklist 17 for identifying psychosocial concerns and improving access to psychology services within a paediatric cardiology clinic. Method: Parents of 561 children (aged 4–17 years) presenting for follow-up of CHD, acquired heart disease, or arrhythmia completed the Pediatric Symptom Checklist 17 as part of routine care; three items assessing parental (1) concern for learning/development, (2) questions about adjustment to cardiac diagnosis, and (3) interest in discussing concerns with a behavioural healthcare specialist were added to the questionnaire. A psychologist contacted the parents by phone if they indicated interest in speaking with a behavioural healthcare specialist. Results: Percentages of children scoring above clinical cut-offs for externalising (10.5%), attention (8.7%), and total (9.3%) problems were similar to a "normative" primary-care sample, whereas fewer children in this study scored above the cut-off for internalising problems (7.8%; p<0.01). Sociodemographic, but not clinical, characteristics were associated with Pediatric Symptom Checklist 17 scores. 17% of the parents endorsed concerns about learning/development, and 20% endorsed questions about adjustment to diagnosis. History of cardiac surgery was associated with increased concern about learning/development (p<0.01). Only 37% of the parents expressing psychosocial concerns reported interest in speaking with a psychologist. Conclusions: The Pediatric Symptom Checklist 17 may not be sensitive to specific difficulties experienced by this patient population. A questionnaire with greater focus on learning/development and adjustment to diagnosis may yield improved utility. Psychology integration in clinics serving high-risk cardiac patients may decrease barriers to behavioural healthcare services.